Pathogenic and genetic characterization of six Indian populations of Colletotrichum sublineolum, the causal agent of sorghum anthracnose - R.V. HIREMATH, H.C. TAILOR, U.S. KUSHWAHA, R.P. THAKUR*, K. MATHUR, V.P RAO, S. CHANDRA, S. SHIVRAMKRISHNAN, S.KANNAN; S. INDIRA, R.R. DWIVEDI (Indian Phytopathology, 2002)
The pathogenic and genetic characterization of populations of C. sublineolum, the causal agent of anthracnose of sorghum, was investigated in isolates from 6 locations in India. Multi-location field evaluation and greenhouse tests were done on 16 sorghum lines that comprised the International Sorghum Anthracnose Virulence Nursery (ISAVN). The lines were tested in a field trial for 4-5 years (1992-96) at 6 locations: Indore, Surat, Patancheru, Dharwad, Udaipur and Pantnagar. Plants were scored for disease reaction (R/MR/S) and for disease severity (on a 1-9 scale where 1 is no lesions and 9 is >75% leaf area covered with lesions) at the soft-dough stage in the field and at the seedling stage in the greenhouse. Significant (P<0.001) differences wereobserved for virulence (disease reaction) and aggressiveness (disease severity) across locations (isolates) and sorghum lines both in field and greenhouse tests. In both tests, isolateXsorghum line interactions were highly significant (P<0.001) suggesting that populations of C. sublineolum at these 6 locations were different. A random amplified polymorphic DNA (RAPD) analysis exhibited genetic dissimilarities among the isolates and these were classified into 6 groups.